Silicon-Based All-Dielectric Metasurface on an Iron Garnet Film for Efficient Magneto-Optical Light Modulation in Near IR Range - Denis M. Krichevsky (MDPI AG, 2021)
All-dielectric nanostructures provide a unique low-loss platform for efficiently increasing light-matter interaction via excitation of the localized or propagating optical modes. Here, we report on the transverse magneto-optical Kerr effect enhancement in an all-dielectric metasurface based on a two-dimensional array of Si nanodisks on a cerium substituted dysprosium iron garnet thin film. We observed up to 15% light intensity modulation under TM modes excitation. The observed magneto-optical effect is nearly independent of the rotation of the light incidence plane with respect to the metasurface. Being compatible with conventional semiconductor technology, our structure holds promise for device applications, such as light modulators, magnetic and chemical sensors.